Scott Fitzgerald’s The Great Gatsby: Critical reception and visual interpretation - Maklad, Ahmed (AUC Knowledge Fountain, 2015)
The thesis explores how the literary status of Fitzgerald’s novel published in 1925 evolved from being dismissed to becoming a canonical work of American Literature after the death of its author. The role of criticism and adaptations and how they intertwined to popularize the novel among the academic elite and the general public is examined. Four critical studies in different decades of recent history are analyzed to show the different approaches to the novel as well as its relation to the American Dream. The thesis suggests that the four critical studies discussed reflect viewpoints impacted by the cultural and socio-economic factors that marked the decade of their appearance: Kermit Moyer (1973), Ross Posnock (1984), Ray Canterbery (1999), and Benjamin Shreier (2007). Their approaches demonstrate the many ways The Great Gatsby can be viewed and thus its richness as a text. The three film adaptations of the novel in turn depict directors’ take on the novel as well as exhibiting the limitations, predilections, and technical possibilities of the time of their production: Nugent’s (1949), Clayton’s (1974), and Luhrmann’s (2013). The controversial aspects of these adaptations as indicated by reviews and articles, which evaluate them as to how they present Gatsby and the American Dream, have increased the debate and the interest in the novel. Though the novel is located in the U.S. in the Roaring Twenties associated with the Jazz Age, it continues to speak to present audience by evoking issues related to class, mobility, ethics, and romance.